Bacterial Profile, Antimicrobial Susceptibility Pattern and Associated Risk Factors of Urinary Tract Infection among Pregnant Women - Saelah Amin, Romaisa Anser, Hidayatullah Memon, Hina Faisal, Samina Tarique, Mehvesh Rehan, Seemab Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary tract infections (UTIs) are common during pregnancy, potentially leading to adverse maternal and fetal outcomes, including preterm labor, low birth weight, and renal complications. Early diagnosis and appropriate treatment are essential, but the antimicrobial resistance patterns in pregnant women have changed over time, complicating treatment decisions. Understanding the bacterial profile and resistance trends is crucial for effective management and prevention strategies. Objective: To identify the bacterial profile, antimicrobial susceptibility pattern, and associated risk factors of urinary tract infection among pregnant women. Methods: This was a cross-sectional study conducted at Rashid Latif Medical College from June 2022 to December 2022, including 245 pregnant women with suspected urinary tract infections, selected through non-probability consecutive sampling. Results: In a cohort of 245 pregnant women, UTIs were predominantly caused by Escherichia coli (58.5%), with significant resistance observed to amoxicillin (72%) and cotrimoxazole (65%). Diabetes (58%), hypertension (70%), and a history of recurrent UTIs were identified as major risk factors for developing UTIs. Clinical outcomes, including premature delivery (12%) and low birth weight (14%), were significantly higher in UTI-positive patients. Logistic regression revealed previous UTI history, diabetes, hypertension, and multiple pregnancies as significant predictors of UTIs during pregnancy. Conclusion: Escherichia coli remains the predominant pathogen in urinary tract infections among pregnant women, but rising antimicrobial resistance to first-line antibiotics underscores the importance of periodic surveillance and individualized treatment regimens. Pregnant women with specific risk factors such as advanced age, multiple pregnancies, and a history of UTIs are more likely to develop UTIs, necessitating targeted screening and preventive measures. Keywords: Urinary tract infection, pregnant women, antimicrobial resistance, bacterial profile, risk factors, Escherichia coli